Strategies for ex situ conservation of Centaurea cineraria subsp. circae (Asteraceae), an endemic plant from Lazio (Italy). (3rd March 2016) - Valletta, A.; Santamaria, A. R.; Fabrini, G.; Tocci, N.; Filho, V. C.; Wagner, T.; Brasili, E.; Pasqua, G.
Abstract : Centaurea cineraria subsp. circae is an endemic plant with a distribution area limited to Circeo mountain (Lazio, Italy), whose population was estimated in a very low number of individuals. The aim of this work was to investigate ex situ conservation strategies such as achene collection and in vitro plant propagation, which will permit to carry out restoration programmes. The test carried out on the achenes demonstrated that only 5.5% of them were morphologically healthy. Seed germination tests showed that seeds do not display dormancy and that germination does not require pre-treatments. The higher germination rate (67.5%) was observed under a photoperiod of 12/12 h (light/dark) and temperature regime +20/+10°C. The in vitro studies demonstrated that micropropagation, acclimatization and the transfer outdoors of C. cineraria subsp. circae are not particularly difficult: 74% of shoot explants in a Murashige and Skoog (MS) medium added with 0.5 mg/l benzylaminopurine and 2 mg/l kinetin formed multiple shoots; 100% of shoots rooted in the MS medium added with 0.5 mg/l indole-3-butyric acid and over 90% survived the acclimatization phase. After been transferred outdoors, the totality of in vitro- propagated plants bloomed and appeared morphologically indistinguishable from wild plants. Preliminary chemical analyses showed a similar profile for in vitro- propagated and wild plants.